Purpose-Driven Navigation - Adabala, Neeharika; Toyama, Kentaro (First international conference on GeoSpatial Semantics, 2005)
Navigation in the context of GIS (Geographic Information Systems) is associated with a sequence of pan and zoom operations that lead to a specific destination. Navigation, in this context, leads a user to an a priori desired destination. There are cases, however, when users may not have a clear idea of a single destination. In this work, we propose richer navigational schemes by augmenting the concept of navigation to be broader than the goal of arriving at a single destination. This is achieved by identifying typical patterns of map use and the purposes behind such patterns, and defining corresponding navigational schemes. The proposed technique enables what we call purpose-driven navigation of maps, e.g., “scan region” or “explore neighborhood”. We present example scenarios that demonstrate the benefit of purpose-driven navigation.